Financial Deepening, Foreign Direct Investment and Output Performance in Nigeria - Alabi Mumeen Olatunbosun; Tella Sheriffdeen Adewale; Odusanya Ibrahim Abidemi; Yinusa Olumuyiwa Ganiyu (Scientific Annals of Economics and Business, 2018)
This study examines the relationship between financial deepening, foreign direct investment and output performance in Nigeria from 1980-2015 using the Autoregressive Distributed Lag (ARDL) Bound Test approach. A long-run relationship was established between financial deepening indicators, foreign direct investment and output performance in Nigeria. Foreign direct investment and market capitalization as a percentage of the GDP exerted significantly on output performance both in the short-run and in the long-run periods. It is recommended that financial depth should be enhanced through improved and highly efficient provision of credit by banks to the real sector of the Nigerian economy.